Turn off that night light! Light-at-night as a stressor for adolescents - Guindon, Grace E.; Murphy, Cloey A.; Milano, Maria E.; Seggio, Joseph A. (Frontiers in Neuroscience, 2024)
Light-at-night is known to produce a wide variety of behavioral outcomes including promoting anxiety, depression, hyperactivity, abnormal sociability, and learning and memory deficits. Unfortunately, we all live in a 24-h society where people are exposed to light-at-night or light pollution through night-shift work -the need for all-hours emergency servicesas well as building and street-lights, making light-at-night exposure practically unavoidable. Additionally, the increase in screentime (tvs and smart devices) during the night also contributes to poorer sleep and behavioral impairments. Compounding these factors is the fact that adolescents tend to be "night owls" and prefer an evening chronotype compared to younger children and adults, so these teenagers will have a higher likelihood of being exposed to light-at-night. Making matters worse is the prevalence of high-school start times of 8 am or earliera combination of too early school start times, light exposure during the night, and preference for evening chronotypes is a recipe for reduced and poorer sleep, which can contribute to increased susceptibility for behavioral issues for this population. As such, this mini-review will show, using both human and rodent model studies, how light-at-night affects behavioral outcomes and stress responses, connecting photic signaling and the circadian timing system to the hypothalamic-pituitary adrenal axis. Additionally, this review will also demonstrate that adolescents are more likely to exhibit abnormal behavior in response to light-at-night due to changes in development and hormone regulation during this time period, as well as discuss potential interventions that can help mitigate these negative effects.